(untitled) (Journal of the College of Basic Education, 2022)
In this work, we investigate and synthesis a (NO2) gas sensing properties of Ferric oxide (Fe2O3) thin films are prepared using magnetron DC- sputtering technique, using different thicknesses concurring various deposition times. Each film is tested with different sample temperature (200, 250 and 300) oC in order to enhance gas sensitivity. The results reveal that the films sensitivity increases as the film thickness decreases (lower grain size), and the gas sensitivity increases also with the increasing operating temperature